Zolimidine Analogues: The Synthesis of Imidazo[1,2-α]pyridine-Based Sulfilimines and Sulfoximines - Hendriks, Christine M. M.; Nürnberg, Pinchas; Bolm, Carsten (Synthesis, 2015)
Zolimidine is a methylsulfonyl-substituted drug with an imidazo[1,2-α]pyridine core used for the treatment of peptic ulcer. Herein, we report the synthesis of unprecedented N-acetylsulfilimine and -sulfoximine analogues under mild conditions. Deprotection of the N-acetylsulfoximine allows the preparation of the corresponding NH-sulfoximine.
Keywords: imidazo[1,2-α]pyridine; sulfoximine; sulfilimine; zolimidine; imination